2023
DOI: 10.3389/fresc.2023.1216281
|View full text |Cite
|
Sign up to set email alerts
|

Combining spinal neuromodulation and activity based neurorehabilitation therapy improves sensorimotor function in cerebral palsy

Rahul Sachdeva,
Kristin Girshin,
Yousef Shirkhani
et al.

Abstract: Motor dysfunction in individuals with cerebral palsy (CP) such as the inability to initiate voluntary movements, walking with compensatory movement patterns, and debilitating spasticity is due to the aberrant neural connectivity between the brain and spinal cord. We tested the efficacy of noninvasive spinal cord neuromodulation (SCiP™, SpineX Inc.) with activity-based neurorehabilitation therapy (ABNT) in improving the sensorimotor function in six children with CP. Children received 8 weeks of either SCiP™ or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 29 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…Our findings build on prior studies of tSCS for children with CP. There have now been evaluations of tSCS with more than 50 children with CP across several research groups [14], [15], [16], [17]. Most prior studies have not evaluated impacts on spasticity or long-term training.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our findings build on prior studies of tSCS for children with CP. There have now been evaluations of tSCS with more than 50 children with CP across several research groups [14], [15], [16], [17]. Most prior studies have not evaluated impacts on spasticity or long-term training.…”
Section: Discussionmentioning
confidence: 99%
“…Most prior studies have not evaluated impacts on spasticity or long-term training. In the one prior study that evaluated spasticity, however, no effect of tSCS on spasticity was reported for the two GMFCS Level I-II children included in the study when tSCS was combined with activity-based neurorehabilitation therapy [15]. They applied tSCS to the cervical and thoracic spine at lower amplitudes (12-18 mA at C5-6 and 10-16 mA at T11-12) All rights reserved.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior work has hypothesized that tSCS supports neuroplasticity by inducing reorganization of the central nervous system [8]. Repeated delivery of the combination of tSCS and physical therapy has led to improvements in gross motor function for children with CP [6,7,9]. Understanding the neuromechanical response to therapeutic tSCS is critical in defining the mechanisms by which spinal stimulation may improve gross motor function.…”
Section: Introductionmentioning
confidence: 99%